EU’s Preferential Trade Agreements: Why Lithuanian Firms Underutilize Them? - Enrika Naujokė (Lex Portus, 2022)
It takes many years to negotiate a Preferential Trade Agreement (PTA). The goal is the economic benefits that utilization of PTAs brings. However, the European Commission found that utilization of some PTAs is very low. This study aimed to reveal what obstacles firms face and to recommend solutions. A literature review was done, and semi-structured interviews were conducted (eight participants were selected using the convenience sampling technique). The research questions were about the extent Lithuanian companies utilize PTAs, what they consider obstacles and how these can be overcome. The review of the literature revealed seven main issues. Semi-structured interviews highlighted one more important issue. One of the most significant issues revealed is the lack of interest of the Lithuanian customs administration in promoting PTAs’ utilization.